First molecular detection of Rickettsia sp. strain Atlantic rainforest in Amblyomma ovale ticks from Espírito Santo state, Brazil - Igor da Cunha Lima Acosta; Hermes Ribeiro Luz; Álvaro Adolfo Faccini-Martínez; Sebastián Muñoz-Leal; Crispim Cerutti Junior; Marcelo Bahia Labruna (Revista Brasileira de Parasitologia Veterinária, 2018)
Abstract Espírito Santo state (southeastern Brazil) is considered an endemic area for spotted fever group rickettsioses. In February 2017, we received in our laboratory seven unfed Amblyomma ovale adult ticks collected by a farmer from his clothes and body (not attached) during a working day in the rural area of Ibiraçu municipality, Espírito Santo state. By polymerase chain reaction (PCR) analyses, targeting gltA and ompA rickettsial genes, the DNA of Rickettsia was detected in 6/7 (85.7%) A. ovale. In all cases, DNA sequencing of PCR products revealed that consensus sequences of both genes were 100% identical to gltA and ompA corresponding sequences of Rickettsia sp. strain Atlantic rainforest retrieved from GenBank. This study reports the first molecular detection of Rickettsia sp. strain Atlantic rainforest in A. ovale ticks from Espírito Santo state. Our findings indicate a new Brazilian state in the southeast region at risk of human infection with this tick-borne emerging rickettsial agent.